Correlation of muscle strength, working memory, and activities of daily living in older adults - Liao, Jinlin; Wang, Jing; Jia, Shuqi; Cai, Zhidong; Liu, Hairong (Frontiers in Aging Neuroscience, 2024)
Objective: This study aims to investigate the relationship between muscle strength, working memory, and activities of daily living (ADL) in older adults. Additionally, it seeks to clarify the pathways and effects of working memory in mediating the relationship between muscle strength and ADL.Methods: Using a cross-sectional study design, we recruited 245 older adults individuals from nursing homes. We collected data on grip strength, the 30-second sit-to-stand test, the N-back task, and ADL. The data were analyzed using independent sample t-tests, χ2 tests, correlation analysis, and structural equation modeling.Results: Grip strength significantly influenced ADL (effect size = -0.175, 95% CI: -0.226 to -0.124). Grip strength also had a significant direct effect on ADL (effect size = -0.114, 95% CI:-0.161 to -0.067). The 1-back task correct rate significantly mediated the relationship between grip strength and ADL (effect size = 0.054, 95% CI: -0.084 to -0.029). The 30-second sit-tostand test significantly impacted ADL (effect size = -0.280, 95% CI: -0.358 to -0.203). It also had a significant direct effect on ADL (effect size = -0.095, 95% CI: -0.183 to -0.007). The 1back task correct rate significantly mediated the relationship between the 30-second sit-to-stand test and ADL (effect size = -0.166, 95% CI: -0.236 to -0.106).There exists a strong correlation between muscle strength, working memory, and ADL. Increased muscle strength leads to better ADL performance and improved working memory tasks. Low cognitive load working memory tasks can mediate the relationship between muscle strength and ADL. Regular physical exercise can enhance muscle strength, slow down the decline of working memory, thereby maintaining or improving ADL in older adults.